Delayed methimazole-induced agranulocytosis in a 6-year old patient with Graves' disease. (December 2016) - Puthenpura, Vidya; Desai, Kinjal; Bauer, Andrew; Marshall, Ian
Abstract Background Agranulocytosis is regarded as a rare side effect of methimazole (MMI) therapy that occurs in a dose dependent manner and that usually develops within the first 3–6 months of treatment. Although delayed development beyond this timeline has been documented in adults, very few children have been reported with this presentation. Case presentation We present a 6-year old patient who developed agranulocytosis 18 months after the start of MMI therapy. Conclusions This is an unusual case of a 6-year old patient who developed this serious side effect on stable MMI therapy well beyond the typical timeline. Our review of the literature revealed that there really is inconclusive data on the incidence, time, and dose-dependency of MMI-induced agranulocytosis in the pediatric Graves' disease population.